Individual and organizational rule-breaking: test of an integrated multilevel model - Karadag, Reha (Journal of business ethics, 2024)
Why do employees break organizational rules and why are organizations unable to prevent this? Past studies have suggested three predictors of rule-breaking: predisposition due to normalization of rule-breaking; pressure due to competitive and performance strain; and opportunity to break the rules due to job characteristics associated with the assigned role and the time at work (e.g., Baucus, 1994). We used a purposive sample of 14,472 observations from 5,735 individuals nested in 199 organizations, to investigate these predictors in a sports context where rule-breaking was likely to be low because of a high risk of detection and a strong compliance system. This allowed us to hold constant the effects of compliance systems and rules that were universally applied in all organizations so that we could compare differences in rule-breaking associated with predisposition, pressure, and opportunity. Compared to previous research, our method permitted us to draw four unique conclusions: (a) all three theories about predictors of rule-breaking were supported, even when all predictors were included simultaneously in a multivariate analysis; (b) individual rule-breaking was predicted by individual and organizational variables in multilevel models, suggesting that employees, the organization, and the industry all support rule-breaking under some conditions; (c) temporal precedence of predictor variables in longitudinal analysis suggested that they influenced current rule-breaking rather than the other way around; and (d) the use of a single-industry sample allowed us to collect nested data from individuals and organizations whose rule-breaking was more likely to be detected and penalized than in other industries, thus reducing undercount of rule-breaking.